Brief Reports: A Distinct DNA Methylation Signature Defines Breast Cancer Stem Cells and Predicts Cancer Outcome. (14th October 2014) - El Helou, Rita; Wicinski, Julien; Guille, Arnaud; Adélaïde, Jose; Finetti, Pascal; Bertucci, François; Chaffanet, Max; Birnbaum, Daniel; Charafe-Jauffret, Emmanuelle; Ginestier, Christophe
Abstract : Self-renewal and differentiation are two epigenetic programs that regulate stem cells fate. Dysregulation of these two programs leads to the development of cancer stem cells (CSCs). Recent evidence suggests that CSCs are relatively resistant to conventional therapies and responsible for metastasis formation. Deciphering these processes will help understand oncogenesis and allow the development of new targeted therapies. Here, we have used a whole genome promoter microarray to establish the DNA methylation portraits of breast cancer stem cells (bCSCs) and non-bCSCs. A total of 68 differentially methylated regions (DMRs) were more hypomethylated in bCSCs than in non-bCSCs. Using a differentiation assay we demonstrated that DMRs are rapidly hypermethylated within the first 6 hours following induction of CSC differentiation whereas the cells reached the steady-state within 6 days, suggesting that these DMRs are linked to early CSC epigenetic regulation. These DMRs were significantly enriched in genes coding for TGF- β signaling-related proteins. Interestingly, DMRs hypomethylation was correlated to an overexpression of TGF- β signaling genes in a series of 109 breast tumors. Moreover, patients with tumors harboring the bCSC DMRs signature had a worse prognosis than those with non-bCSC DMRs signature. Our results show that bCSCs have a distinct DNA methylation landscape with TGF- β signaling as a key epigenetic regulator of bCSCs differentiation. Stem Cells   2014;32:3031–3036